Commentary and Translation: Exploring the Du lü yanyi 杜律演義 - Barbara Bisetto (Acta Universitatis Carolinae: Philologica, 2018)
This paper presents a preliminary discussion of the status of translation practices embedded in the commentarial entries of the Yuan dynasty anthology Du lü yanyi 杜律演義 [Explanation of the Meaning of Du Fu’s Regulated Verse] by Zhang Xing 張性. The research moves from a definition of ‘translation’ that extends beyond the prototypical discourse on the relations between different languages to encompass more varied discursive processes and products within a single language and more extensively within the field of metaliterature. As a case study, the paper examines the characteristics of the commentarial entries appended to two poems of the sequence “Qiu xing ba shou 秋興八首” [Stirred by Autumn] in the anthology Du lü yanyi. It analyses how the commentarial notes are related to units or whole portions of the poetic prototext, and for what purpose. As a result, the paper brings to light the juxtaposition and the combination of two fundamental approaches to the mediation of the prototext: one leaning towards commentary by way of explanatory reformulations, and the other leaning towards translation in the form of imitative reformulations.